The economics and politics of international preservation collaborations: a Malian case study - Dong, Lorraine (Archival Science, 2012)
This paper examines four economic and political themes that are relevant to international heritage preservation and archives efforts. Collaborations that involve multiple players such as industrialized nations, international heritage organizations, and postcolonial or economically developing regions will inevitably be laden with sociopolitical and economic entanglements that affect preservation outcomes and modern cultural development. Drawing on the Timbuktu Manuscripts Project in Mali for context, the paper will first discuss the infrastructural limitations that limit the progress and sustainability of projects that seek to preserve and create greater access to cultural heritage. The second critical theme is the enduring legacy of colonialism and, more specifically, the multiple concepts in Africa regarding cultural and historical evidence. The third theme is the compromise between local and global development advocates, especially in terms of agreeing on access boundaries to cultural materials. The fourth theme is the dialogue that must take place between stakeholders, especially between the host communities and supporting entities. This paper posits that it is necessary to look at the Timbuktu Manuscripts Project and other heritage preservation and archives projects by their high-level commonalities and through deeply contextualized historical lenses in order to cogently discuss the social value of these multinational projects and to help plan future collaborative efforts.
Keywords: A&DwP website; Archives; Cultural heritage; Digitization; Mali; Preservation; Timbuktu